Creation of hot dense matter in short-pulse laser-plasma interaction with tamped titanium foils - Chen, SN; Gregori, G; Patel, P; Chung, H; Evans, R; Freeman, R; Saiz, E; Glenzer, S; Hansen, S; Khattak, F; King, J; Mackinnon, A; et al. (2007)
Dense titanium plasma has been heated to an electron temperature up to 1300 eV with a 100 TW, high intensity short-pulse laser. The experiments were conducted using Ti foils (5 μm thick) sandwiched between layers of either aluminum (1 or 2 μm thick) or plastic (2 μm thick) to prevent the effects of prepulse. Targets of two different sizes, i.e., 250 × 250 μm 2 and 1×1 mm2 were used. Spectral measurements of the Ti inner-shell emission, in the region between 4 and 5 keV, were taken from, the front-side (i.e., the laser illuminated side) of the target. The data show large shifts in the Kα emission from open-shell ions, suggesting bulk heating of the sample at near solid density, which was largest for reduced mass targets. Comparison with collisional radiative and 2D radiation hydrodynamics codes indicates a peak temperature of Te,peak= 1300 eV of solid titanium plasma in ∼0.2 μm thin layer. Higher bulk temperature (T e,bulk=100 eV) for aluminum tamped compared to CH tamped targets (Te,bulk=40 eV) was observed. A possible explanation for this difference is described whereby scattering due to the nuclear charge of the tamping material leads to modified electron transport behavior. © 2007 American Institute of Physics.